Effect of temperature on the leaching of heavy metals from nickel mine tailings in the arctic area, Norway - Fu, Shuai; Lu, Jinmei; Walder, Ingar; Wu, Daishe (International Journal of Agricultural and Biological Engineering, 2023)
The leaching of heavy metals from tailings deposit due to the oxidation of sulphidic tailings and formation of acidic leachate is considered a high risk to the surrounding environment. Temperature plays an important role in the leaching of heavy metals from tailings in changing acid-based environment, especially in the Arctic area. To investigate how the temperature variation affected metal release from tailings in the Arctic area, a series of column leaching experiments was conducted under four temperature situations (5°C, 10°C, 14°C and 18°C). Physicochemical properties, Fe, Zn, Ni and Mn concentrations of leachates at each cycle were measured, and multivariate statistical analysis was applied to research the effect of temperature on heavy metals leaching from tailings in the Arctic area. The results showed that higher temperatures encouraged tailings to oxidation and sulfuration of and promoted heavy metal release from the tailings through precipitation and erosion. Ni, Zn and Mn have similar releasing resources from tailings and positive correlation in the leaching activity. Rising temperature accelerated Fe leaching; Fe leaching promoted leaching of the other metals, especially of Mn. Appropriately increase temperature will accelerate oxidization and sulfidization of the tailings, promote acid generation and increase TDS and, finally, promote the release of heavy metals. Climate change, with rising temperatures increasing the risk of heavy metals leaching from the tailings, should be given greater attention. Keeping tailings away from the appropriate temperature and in a higher alkalinity is a good method to control the leaching of heavy metals from tailings. Keywords: tailings, heavy metals, leaching, temperature, Norway DOI: 10.25165/j.ijabe.20231602.7216 Citation: Fu S, Lu J M, Walder I, Wu D S. Effect of temperature on the leaching of heavy metals from nickel mine tailings in the arctic area, Norway. Int J Agric & Biol Eng, 2023; 16(2): 152－158.